“Migrationland”: Social and Economic Impacts of Demographic Churn in Maine and Cumberland County Post-Pandemic - Bouvier, Rachel; Grandbois, Joie (Maine Policy Review, 2025)
Maine is experiencing a historic demographic transformation fueled by the rise of remote work, pandemic-driven migration, and growing concerns about climate change. This article examines recent migration trends in Maine—particularly Cumberland County—using IRS migration data to analyze who is moving, where they are coming from, and how these shifts are reshaping the region. Findings reveal a significant influx of higher-income newcomers, with implications for housing affordability, income inequality, and local labor markets. While these shifts present opportunities for revitalization, they also pose challenges related to equity, cultural cohesion, and infrastructure strain. The article explores these dynamics through the lenses of economic vitality, social equity, and fiscal impact, offering insights and policy recommendations to help Maine communities adapt to rapid demographic churn.